3
$\begingroup$

Let $x \in \mathbb{R}^{n}$ and $A(t) \in \mathbb{R}^{n\times n}$. If $\dot{x}=A(t)x$ and $\dot{x}=cA(t)x$ with $c>1$ are exponentially stable. Is the convergence rate of $x$ to zero of $\dot{x}=cA(t)x$ faster than that of $\dot{x}=A(t)x$?

This question is initially asked on Mathematics: https://math.stackexchange.com/questions/2881136/is-the-convergence-of-dotx-2atx-faster-than-that-of-dotx-atx

Here is my initial thought:

For linear time-invariant system, the fact $\dot{x}=A(t)x$ is exponentially stable implies $A(t)=A$ is Hurwitz. It is clear that the $i$th eigenvalue $\lambda_{i}(cA)=c\lambda_{i}(A)$, $i,\ldots,n$, thus, the convergence for $\dot{x}=cAx$ with $c>1$ is faster than that of $\dot{x}=Ax$.

For a linear time-varying system. Let us consider the extreme case where $c=0$, $\dot{x}=cA(t)x=0$, which implies it is no longer exponentially stable.

For $c>1$, can we have the same conclusion for exponentially stable linear time-varying systems, i.e., can we conclude that the convergence is faster when $c>1$?

Update 1: For a scalar time-varying system, i.e., $x\in\mathbb{R}$. We can actually prove this conjecture. In fact, from the uniqueness of the equilibrium point ($x=0$ is the only solution that renders $\dot{x}=0$), the solution of $\dot{x}=ca(t)x$ is a monotone function either strictly increasing or strictly decreasing, depending on its initial condition $x(0)$. Thus, for $\dot{x}=ca(t)x$ where $c>1$, the absolute value of the derivative is larger than that of $\dot{x}=a(t)x$, while for both cases the sign of $\dot{x}(t)$ remains unchanged for all $t\ge0$. Thus, $\dot{x}=ca(t)x$ does converge faster to $x=0$ than $\dot{x}=a(t)x$.

$\endgroup$
  • 1
    $\begingroup$ Math.SE user AVK provides a possible counterexample here, did you check it? Also, even in dimension one highly oscillatory coefficients of the form $A(t)=c \sin(e^t)$ may lead to exponentially fast convergence to a non-zero value $e^{c\pi/2} x(0)$, with convergence rate independent of $c$, but I suppose this is not what you had in mind. $\endgroup$ – Mateusz Kwaśnicki Sep 11 '18 at 11:20
  • $\begingroup$ The counterexample considered $c\in(0, 0.55)$, while the questions focus on $c\in(1,\infty)$. The assumption exponential stability of $\dot{x}=A(t)x$ implies that $x(t)$ will convege to the origin as $t$ tends to infty. Thus, $A(t)=c\sin(e^{t})$ does not satisfy the above assumption. $\endgroup$ – guluzhu Sep 11 '18 at 11:28
  • $\begingroup$ I think AVK's counterexample may work if you substitute $\tfrac{1}{4}A(t)$ for $A(t)$. Still, apparently there is a simpler counterexample that I describe in my answer. $\endgroup$ – Mateusz Kwaśnicki Sep 11 '18 at 19:55
5
$\begingroup$

A simple counterexample can be constructed as follows: take $$ A(t) = \pmatrix{0&\tfrac{\pi}{2}\\-\tfrac{\pi}{2}&0} \qquad \text{for } t \in [2n, 2n+1) ,$$ and $$ A(t) = \pmatrix{-\alpha&0\\0&-\beta} \qquad \text{for } t \in [2n+1, 2n+2) ,$$ where $0 < \alpha \leqslant \beta$.

The equation $x'(t) = c A(t) x(t)$ describes then the following evolution: during each of the intervals $[2n, 2n+1)$ the particle is rotated by an angle $\tfrac{c \pi}{2}$ counter-clockwise, while during the interval $[2n, 2n+1)$ each of the coordinates converges exponentially to zero at rate $c \alpha$ or $c \beta$.

For $c = 1$ (or, more generally, for odd values of $c$), rotation essentially swaps the coordinates (if we disregard signs), so effectively $$x(4n) = (-1)^n e^{-c(\alpha + \beta) n} x(0).$$ The rate of convergence is thus $\tfrac{1}{4} c (\alpha + \beta)$.

For $c = 2$ (or, more generally, for even values of $c$), rotation merely changes the sign, so we end up with $$x(4n) = \pmatrix{e^{-2c\alpha n}&0\\0&e^{-2c\beta n}} x(0).$$ Rate of convergence is therefore $\tfrac{1}{2} c \alpha$.

Choose $\alpha = 1$ and $\beta = 7$. Then solutions of $x'(t) = A(t) x(t)$ converge to zero at rate $\tfrac{1}{4} \times 1 \times (1 + 7) = 2$, while solutions of $x'(t) = 2 A(t) x(t)$ converge to zero at slower rate $\tfrac{1}{2} \times 2 \times 1 = 1$.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thank you for the counterexample. My follow-up questions is: Does the conjecture hold for sufficiently large $c$? $\endgroup$ – guluzhu Sep 12 '18 at 1:05
  • $\begingroup$ @guluzhu: I do not know the answer. Sounds plausible, at least in dimension two. $\endgroup$ – Mateusz Kwaśnicki Sep 12 '18 at 7:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.